2003
DOI: 10.4049/jimmunol.170.8.4201
|View full text |Cite
|
Sign up to set email alerts
|

Host Absence of CCR5 Potentiates Dendritic Cell Vaccination

Abstract: Previous work has shown that dendritic cells (DCs) express specific chemokine receptors that allow for coordinated movement in vivo. To test the in vivo relevance of this, we used a murine melanoma system and knockout mice to investigate the function of the chemokine receptor CCR5 and its ligands, CCR ligand (CCL)3 and CCL5. We found that the lack of CCR5 in the host mouse resulted in delayed tumor growth, but this effect was overcome at a higher tumor load. With the administration of tumor charged DCs, CCR5−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
(17 reference statements)
3
19
1
Order By: Relevance
“…In concordance with our results indicating a protumoral role of CCR5/CCR5 ligands in cancer, CCL5 secretion by mesenchymal stem cells enhanced the metastatic potential of breast cancer (46). Ng-Cashin et al (47) demonstrated that the deficiency of CCR5 or its ligand CCL3 resulted in delayed or accelerated melanoma growth depending on the tumor load. Furthermore, in a mouse model of pancreatic adenocarcinoma, knockdown of CCL5 production in tumors resulted in the delayed tumor growth (20).…”
Section: Discussionsupporting
confidence: 80%
“…In concordance with our results indicating a protumoral role of CCR5/CCR5 ligands in cancer, CCL5 secretion by mesenchymal stem cells enhanced the metastatic potential of breast cancer (46). Ng-Cashin et al (47) demonstrated that the deficiency of CCR5 or its ligand CCL3 resulted in delayed or accelerated melanoma growth depending on the tumor load. Furthermore, in a mouse model of pancreatic adenocarcinoma, knockdown of CCL5 production in tumors resulted in the delayed tumor growth (20).…”
Section: Discussionsupporting
confidence: 80%
“…For example, CCR5-deficient mice (ccr5 Ϫ/Ϫ ) infected with Mycobacterium tuberculosis have more dendritic cells in lymph nodes and increased pulmonary inflammation due to a greater T-cell response than ccr5 ϩ/ϩ mice (2). Similar data have been reported for mouse models of Listeria and lymphocytic choriomeningitis virus infections, as well as for enhanced responses to a melanoma dendritic cell vaccine (25,26,39). How CCR5 restrains the immune response is unknown.…”
supporting
confidence: 72%
“…ϩ and CD8 ϩ T-cell responses to a variety of antigens and to a dendritic cell vaccine (25,26,39). Such findings suggest that CCR5 may behave as a negative regulator of T cells in an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…DCs were derived from bone marrow progenitor cells in the presence of GM-CSF and IL-4 [19]. On day 7 of culture, immature DCs were harvested and cryopreserved in 90% FBS/10% DMSO.…”
Section: Generation Of Vrp-dc Vaccinesmentioning
confidence: 99%